Optimized PV-Battery Systems using Backtracking Search Algorithm for Sustainable Energy Solutions - Abdolrasol M.G.M.; Jern Ker P.; Hannan M.A.; Tiong S.K.; Ayob A.; Almadani J.F.S. (Institute of Electrical and Electronics Engineers Inc., 2024)
This study explores the integration of photovoltaic (PV) systems with battery storage for sustainable energy solutions. Employing the Backtracking Search Algorithm (BSA), the research optimizes PI controller parameters to enhance system efficiency and reliability. Real-world energy demand and weather data are integrated for practical relevance. Rigorous simulations within MATLAB/Simulink establish a robust analytical framework, evaluating optimization algorithms and identifying optimal configurations. By analysing objectives and simulation outcomes, the study provides insights for system refinement. The research strategically applies advanced algorithms to elevate PV-battery system performance and compares outcomes with Particle Swarm Optimization (PSO) and other studies, offering a comprehensive benchmark for evaluation. 2023 IEEE.